To skandinaviske evighetskalendere i samlingen til Det etnografiske museet i Poznań - Lange, Tadeusz Wojciech (Folia Scandinavica Posnaniensia, 2009)
The article features two Scandinavian calendar clogs from the Ethnographic Division of the National Museum in Poznań. Perpetual wooden calendars are known from several European countries, but only in Scandinavia were they made in large numbers. Two distinctly different types of calendar clogs are known: the simple ‘agricultural almanac’ type, characteristic of Norway, and a more sophisticated computing variety (with golden numbers), found chiefly in Sweden. The Poznań clogs are described in detail and identified as Swedish runic staffs: one is heptagonal, dating from 1599 and made in the Linköping area; with the other being flat, sword-like, possibly equally old, originating from the district of Uppland.